Behavioral Neuroscience: Crawling Is a No-Brainer for Fruit Fly Larvae. - Riedl, J.; Louis, M. (Current Biology, 2012)
How are stereotyped behaviors organized in a simple nervous system? A new study in the Drosophila larva reports that the foraging routine can be performed in the absence of any input from the brain.